Fast Unmixing of Noisy Hyperspectral Images Based on Vertex Component Analysis and Singular Spectrum Analysis Algorithms. Issue 1 (2nd January 2020) - Song, Dongmei; Sun, Ning; Xu, Mingming; Wang, Bin; Zhang, Ling
Abstract: Efficient denoising is of great significance to unmixing hyperspectral images. In the present study, a fast unmixing method for noisy hyperspectral images based on the combination of vertex component analysis and singular spectrum analysis is proposed. First, the noisy endmember spectra are extracted by using the vertex component analysis algorithm. Then the singular spectrum analysis is used to denoise the endmember spectrum. When compared with the hyperspectral data as a whole, the amounts of endmember spectral data are known to be small. If only denoising endmember spectral data were to be performed, then the denoising time will be greatly improved, and image information can be effectively preserved. The method has high precision and fast speed for unmixing the noisy hyperspectral image. The advantages of this method will be more apparent when dealing with large amounts of hyperspectral data. In this article, different noise images are experimented with using this method, and strong experimental results are obtained.